Influence of N-acetylcysteine on hepatic amino acid metabolism in patients undergoing orthotopic liver transplantation - Zapletal, Christina; Martin, Eike; Dröge, Wulf (Transplant international, 2001)
Experimental treatment with the antioxidant and glutathione precursor N-acetylcysteine (NAC) has been performed in orthotopic liver transplantation (OLT) to reduce reperfusion injury. To investigate the effect of NAC on the hepatic and intestinal amino acid metabolism, intraoperative amino acid exchange rates were studied in liver transplant recipients with high dose NAC treatment (n= 10) and in control patients (n= 9). Treatment with NAC was found to cause a loss of amino acids and increased urea nitrogen release from the liver graft. The net balance of most amino acids was shifted to increased hepatic release or decreased hepatic uptake. The initial cumulative splanchnic release of all proteinogenic amino acids in the NAC treated group was significantly higher than in the control group. These findings are tentatively explained by an increased net protein catabolism in the liver. The increased hepatic urea and glutamine production rate of the NAC treated patients is expected to increase the energy and oxygen demand of the liver in this critical situation. Thus, NAC may have caused marked metabolic disturbances in the freshly implanted graft. The dosage of NAC should therefore be modified to avoid these disadvantages.
Online veröffentlich: 11. März 2005
Gesehen am 03.02.2021
Elektronische Reproduktion der Druck-Ausgabe